Analisa Perancangan Sistem Informasi Keuangan Pegawai pada BASARNAS Gorontalo - Anisa Larasati Panyilie; Ayu Rakhma Wuryandini; Niswatin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the design of the employee financial information system at BASARNAS Gorontalo and the financial reporting system mechanism that operates in accordance with Minister of Finance Regulation (PMK) No. 232/PMK.05/2022 of 2022 concerning Institutional Accounting and Financial Reporting Systems. This research uses a qualitative method with a descriptive approach using primary data sources obtained directly from the field, observations and interviews as well as documentation data. The research location is at BASARNAS Gorontalo JL. Pangeran Hidayat II, Pulubala, Kota Tengah. The results of the research conducted show that the Analysis of the Design of the Employee Financial Information System at BASARNAS Gorontalo has been carried out in accordance with the applicable Minister of Finance Regulations (PMK). And also the system that is running is in accordance with the established Financial Reporting Agency Standards. The Financial Information System Reporting Model has used the Input Sub system via the Tunkin2019 BASARNAS digital application as well as the BASARNAS Online Presence application and the Output Sub system via the SAKTI BASARNAS and DIGIT websites/links from both agencies and the Minister of Finance of Gorontalo City.